Administrative Law Enforcement in Business Licensing Governance: An Empirical Study of Kabupaten Buleleng - Made Ayu Viska Herawati (jfpublisher, 2026)
Licensing constitutes a fundamental instrument in the administration of government, functioning simultaneously as a mechanism for control, supervision, and the protection of public interests in business activities. In the context of regional autonomy, administrative law enforcement in business licensing is essential to ensuring legal certainty, spatial planning order, and sustainable development, particularly in Kabupaten Buleleng, which has experienced significant growth in the tourism and investment sectors. This study employs empirical legal research with a juridical-sociological approach, supported by the statute approach and the conceptual approach. Data were obtained through library research and direct interviews with relevant regional government officials, and subsequently analyzed using a qualitative descriptive-analytical method. The findings indicate that administrative law enforcement is implemented through a graduated pattern of supervision and guidance prior to the imposition of sanctions. Supervision is conducted through the OSS system and cross-agency coordination, while guidance is administered through graduated warning letters and the provision of grace periods for the fulfillment of licensing commitments. This approach reflects the ultimum remedium principle and the preventive legal protection framework in administrative law, consistent with law enforcement theory and the theory of governmental responsibility. However, implementation continues to face obstacles including budgetary limitations, geographical conditions, and inter-agency coordination gaps, which affect the optimization of supervision and the consistency of enforcement. Strengthening institutional capacity and inter-agency coordination mechanisms is therefore essential to improving the effectiveness of administrative law enforcement in regional business licensing governance.